Neisseria gonorrhoeae Limits Chlamydia trachomatis Inclusion Development and Infectivity in a Novel In Vitro Co-Infection Model - Onorini, Delia; Borel, Nicole; Schoborg, Robert V.; Leonard, Cory Ann (Frontiers in Cellular and Infection Microbiology, 2022)
Chlamydia trachomatis (Ct) and Neisseria gonorrhoeae (Ng) are the most common bacterial sexually transmitted infections (STIs) worldwide. The primary site of infection for both bacteria is the epithelium of the endocervix in women and the urethra in men; both can also infect the rectum, pharynx and conjunctiva. Ct/Ng co-infections are more common than expected by chance, suggesting Ct/Ng interactions increase susceptibility and/or transmissibility. To date, studies have largely focused on each pathogen individually and models exploring co-infection are limited. We aimed to determine if Ng co-infection influences chlamydial infection and development and we hypothesized that Ng-infected cells are more susceptible to chlamydial infection than uninfected cells. To address this hypothesis, we established an in vitro model of Ct/Ng co-infection in cultured human cervical epithelial cells. Our data show that Ng co-infection elicits an anti-chlamydial effect by reducing chlamydial infection, inclusion size, and subsequent infectivity. Notably, the anti-chlamydial effect is dependent on Ng viability but not extracellular nutrient depletion or pH modulation. Though this finding is not consistent with our hypothesis, it provides evidence that interaction of these bacteria in vitro influences chlamydial infection and development. This Ct/Ng co-infection model, established in an epithelial cell line, will facilitate further exploration into the pathogenic interplay between Ct and Ng.